Thermodynamic calculations of possible reaction between cobalt di arsenide with couples sulphur - Zhumabekova, N.N.; Zhumabekova, V.N.; Turlibekova, G.K. (Recent Contributions to Physics, 2012)
This paper studied the method of thermodynamic analysis of the possible reactions of cobalt sulphidation di-arsenide (CoAs2) elemental sulfur